Aerosol Optics Light Absorption and Scattering by Particles in the Atmosphere - Kokhanovsky, Alexander A. (Environmental Sciences, 2008)
In Aerosol Optics, Alexander Kokhanovsky provides a comprehensive review of available techniques for the remote sensing of aerosols. Although mostly satellite remote sensing is considered, ground-based techniques are also discussed. The work is founded on the solid basis of radiative transfer theory, coupled with Maxwell theory for the calculation of the scattering properties of small particles. IN particular, the author describes techniques for the determination of the column concentration of aerosol particles and their optical sizing using spaceborne optical instrumentation. The majority of the techniques described in this book use a so-called "library method". This method relies upon the precalculated top-of-atmosphere reflectances (TOAR) for vaious atmospheric aerosol types. The comparison of measured and calculated TOARS allows one to characterize the optically-equivalent aerosol state.